Accounting accruals, heterogeneous investor beliefs, and stock returns - Peng, Emma Y.; Yan, An; Yan, Meng (Journal of Financial Stability, 2016)
We study how a firm's accounting accruals affect the heterogeneity of investor beliefs on the firm's value and further affect the firm's future stock returns. We document three findings. First, we find that the level of the heterogeneity in investor beliefs on a firm's value is higher when the firm experiences a larger increase in its accounting accruals. Second, we find that future stock returns following the earnings announcement are lower when the firm's accounting accruals increases the heterogeneity of investor beliefs to a larger degree. Finally, we also find that the effect of the accruals-induced heterogeneous investor beliefs on future stock returns is more pronounced when short-sale constraints are more binding. Overall, our empirical findings suggest that accounting accruals are a key determinant of the heterogeneity of investor beliefs. They also suggest a channel of investor beliefs whereby accruals affect future stock returns by affecting the heterogeneity of investor beliefs.